2014
DOI: 10.1007/s00204-014-1349-9
|View full text |Cite
|
Sign up to set email alerts
|

Time course of lung retention and toxicity of inhaled particles: short-term exposure to nano-Ceria

Abstract: Two Ceria nanomaterials (NM-211 and NM-212) were tested for inhalation toxicity and organ burdens in order to design a chronic and carcinogenicity inhalation study (OECD TG No. 453). Rats inhaled aerosol concentrations of 0.5, 5, and 25 mg/m3 by whole-body exposure for 6 h/day on 5 consecutive days for 1 or 4 weeks with a post-exposure period of 24 or 129 days, respectively. Lungs were examined by bronchoalveolar lavage and histopathology. Inhaled Ceria is deposited in the lung and cleared with a half-time of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
108
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(120 citation statements)
references
References 65 publications
11
108
0
1
Order By: Relevance
“…In a previous La 2 O 3 toxicity study, high toxicity was observed both in vivo and in vitro , as the particle size decreased and the surface area increased (Lim, ). Several toxicity studies using ultrafine particles reported that a smaller particle size induced higher toxicity (Duffin et al, ; Sager and Castranova, ; Toya et al, ; Keller et al, ; Lim et al, ; Peng et al, ). Therefore, the present study was performed to determine the potential toxicity and target organs of the nano‐sized La 2 O 3 after 28‐day repeated inhalation exposure in Sprague‐Dawley rats, and to provide reference data for further inhalation toxicity studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous La 2 O 3 toxicity study, high toxicity was observed both in vivo and in vitro , as the particle size decreased and the surface area increased (Lim, ). Several toxicity studies using ultrafine particles reported that a smaller particle size induced higher toxicity (Duffin et al, ; Sager and Castranova, ; Toya et al, ; Keller et al, ; Lim et al, ; Peng et al, ). Therefore, the present study was performed to determine the potential toxicity and target organs of the nano‐sized La 2 O 3 after 28‐day repeated inhalation exposure in Sprague‐Dawley rats, and to provide reference data for further inhalation toxicity studies.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, the lung concentration of lanthanum on day 3 decreased by 29% after 13 weeks when nano‐sized La 2 O 3 was given by intratracheal instillation at 5 mg/kg in rats (Lim, ); moreover, the elimination rate was slower than that of our study, possibly because a deeper part of the lung was exposed to the particles after intratracheal instillation. Keller et al () reported that the CeO 2 nanoparticles half‐life in the lung was 40 days in rats were exposed to 0.5 mg/m 3 for 4 weeks. This was similar to the result of our study, where the half‐life of nano‐sized La 2 O 3 in the lung was calculated to be around 30–60 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The growing rate of nanoparticle-based product developments has raised worldwide apprehension regarding the release of MNPs into the environment and their subsequent uptake. There are several uptake pathways for MNPs, which complicates the issue of modelling exposure risks tremendously [5, 15, 30, 40, 54, 60, 83]. Nano-safety studies have seen an exponential rise over the past two decades, but the effects and dangers of nanoparticles, either for animals, humans, or cell structures, are still not clearly defined [10, 43].…”
Section: Introductionmentioning
confidence: 99%
“…The long-term experiment was preceded by a 28-day Subacute Inhalation Toxicity pilot study according to OECD TG 412 (Keller et al 2014). Here, it was intended to establish appropriate doses, representative for the range of low level environmental and occupational exposure scenarios via intermediate particle concentrations, representing a potential threshold above which overload conditions in the lung might exist, to a high exposure concentration for which overload-impaired particle clearance was certainly anticipated.…”
Section: Introductionmentioning
confidence: 99%